Pengelolaan Kredit Usaha Bagi Usaha Mikro dan Kecil Pemula di Setu Babakan Kecamatan Jagakarsa - Harisman Harisman; Reny Andriyanty; Ahmad Nurdin Hasibuan (Jurnal Pemberdayaan Masyarakat, 2023)
The target community for this service activity community was 20 entrepreneurs who have businesses in Setu Babakan Cultural Tourism Village, Jagakarsa District, South Jakarta.  The average participants sell food and drinks along the Setu Babakan cultural tourism.  The method was counseling, to increase the knowledge of the target community regarding proper credit management in order to avoid business debt. The activity consists of two main activities, namely counseling and discussion.  The main factors for the business were at a level of production volume, in order to finance the expansion of business scale where business capital was insufficient. It will be more profitable if the business obtains capital from the other party.  However, the decision to borrow capital, they must consider the prevailing interest rate and the rate of return on investment.  Analysis of the data showed an increase in understanding of good business credit management among the target community.  Before the counseling was conducted, the average level of understanding was 41% and after the counseling, their understanding increased to be 61 percent.  The activity recommended that activities must be sustained in the target communities who have at least a high school education and are between 21-40 years old.